Factors involved in adopting mobile banking for Sharia Banking Sector using UTAUT 2 - Yuliana, Putri Dewi; Aprianingsih, Atik (Jurnal Keuangan dan Perbankan, 2022)
The technology development and covid 19 that hit in 2020 have triggered an increase in digital transactions in Indonesia in recent years. The condition of the Indonesian people, which is dominated by the productive age classified as digital savvy, further strengthens the opportunities and challenges for digital transformation in almost all industrial fields. This study was aimed at determining the important factors for consumers in behavioral intentions to adopt mobile banking. The model examining the factors in this study used constructs in the unified technology acceptance user technology (UTAUT) extension theory, UTAUT 2. The other constructs were perceived value for non-monetary value and perceived credibility, which was an additional construct to predict behavioral intentions. This study used a questionnaire involving 305 respondents randomly as a cross-generational sampling in Indonesia. Structural Equation Method (SEM) and smartPls 3.0 software were used to analyze the data. It was found that perceived value was the strongest predictor of an individual's behavioral intention to adopt mobile banking. Furthermore, performance expectancy, facilitating conditions, habit and perceived credibility (except effort expectancy, social influence and hedonic motivation) were also significant predictors of consumer behavioral intentions. This research is expected to shed insight into the adoption of mobile banking and can help the banking industry, in particular Sharia banking in Indonesia, in launching a strategy to increase market share through digitalization of banking, especially mobile banking services.